Go-Gallon App With A Star (A*) Algorithm Implementation Using Android Kotlin - Khusaeri Andesa; Herwin Herwin; Torkis Nasution (Universitas Islam Kuantan Singingi, 2022)
The need for drinking water now is not to boil water, but to buy it in the form of gallon bottles, which are available wherever it is sold, either at the refill of water or in the supermarket. In a housing estate with many heads of families, it is also difficult to find and obtain water in gallon bottles under certain conditions, and there is also the problem that there is only one brand of gallon bottles, which also makes it difficult to obtain. For this reason, the author provides a solution by creating a go-gallon application with the application of the A-Star (A*) algorithm to be able to detect the service takers of the nearest people, which is basically intended for residential environments, where with this application others can ask to find and purchase gallons and then deliver them to their homes. The A-Star algorithm is one of the distance search algorithms that has an optimal and complete ability to solve problems related to finding or determining a route with the least distance. The hope is that with this application, especially housewives, there is no need to worry when they run out of gallons of drinking water at home, enough with this application, these problems can be overcome.